Branding, Artificial Intelligence, dan Tradisi Berdesa dalam Membangun Kinerja Inovasi BUMDesa - Endang Purwaningsih; Muhamad Fathurahman; Basrowi Basrowi; Nabila Salim; Achmad Said Agil (GUYUB: Journal of Community Engagement, 2024)
The purpose of this PkM is to empower partners in terms of law, management and technology, the focus of community service is to build an innovative spirit to support brand implementation, the community service team created a company profile website as well as e-commerce bumdeskadumaneuh.com, registered a trademark, while Artificial Intelligence is used to build an innovative creative spirit, which supports brand implementation, which ultimately supports measurable innovation performance from the dimensions of managerial innovation, process and product. Strengthening Village Traditions has an impact on the resilience and sustainability of BUMDesa, so innovation based on village inclusivity supported by the application of AI, branding optimization based on trademark ownership, is expected to be able to boost the commercialization of BUMdesa Kadumaneuh products. This PkM activity has been carried out using training and counseling methods as well as assistance in law, IT, and marketing management. Partner knowledge has also increased by an average of above 30%, and legal, management and technology problems have been resolved well. The outputs achieved are the availability of a web company profile along with e-commerce https//bumdeskadumaneuh.com and AI access to support product and service innovation, the registration of the trademarks "Nah&Neh" and "du Maneuh" for pandan mat and Emping Mlinjo producers, improving managerial quality and efficiency, increasing BUMDesa performance, and increasing the empowerment of partner services in the commercialization of micro-business products